A comparative study of reality-based shows in GMA and ABS-CBN networks. - Naig, Zenneth Rowellyn P
Reality TV Shows are usually seen on television nowadays. Starstruck, Extra Challenge, Victim Extreme, Pinoy Pop Superstar, Star In A Million, and Star Circle Quest are some of the Reality TV Shows that teenagers love to watch. Aside from its good-looking participants and hosts there also other reasons why teenagers love to watch these kinds of programs. This Broadcast Research entitled "A Comparative Study of Reality-Based Shows in GMA and ABS-CBN Networks.", This study aims to identity and describe the different reality-based shows GMA and ABS-CBN, determine the different elements Reality TV shows present on both stations and determine the audience preference in watching reality-based programs aired by GMA and ABS-CBN. This study was conducted in the Municipality of Oton. The researchers selected ten (10) barangays that were far from the town proper and the non-availability of cable connections/networks. In every barangay there is twenty (20) high school respondents. All in all, the study has 200 respondents. The researchers used frequency counts and percentage s in analyzing the data gathered. With these, they were able to know which of the Reality TV shows got the highest rank. This study found out that over-all, Extra Challenge got the highest rating among the weekday-aired Reality TV shows (Extra Challenge, Starstruck, Victim Extreme, Star Circle Quest). On the other hand, Star in a Million got a higher rating compared with Pinoy Pop Superstar on weekend-aired Reality TV shows. Extra Challenge of GMA network was considered the best Reality TV show since this was most watched by the respondents coming from the ten (10) chosen barangays of the Municipality of Oton.